A New Key Delivery Method in Wireless Network - Çağatay Ay (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The development of networking technologies and the increase of digital devices have made multimedia transmission quick and easy. However, digital data transmission over open communication channels has introduced a number of security implications, such as copyright infringement and fraud. Due to this reason, the methods and techniques developed for secure data transmission gain importance. Steganography, one of these techniques, can be described as one of the subdivisions of information concealment, which makes data linkage to a carrier that seems harmless for occult communication. The methods and techniques of hiding data who are known by non system users will affect the secure data communication negatively. The inadequacy of the steganography on the security makes encryption important. The secret communication to be made with open communication channels needs to be supported by various steganographic methods and encryption algorithms. In this work, a method has been developed that utilizes network steganography for secure key distribution over network channels. Experimental results have shown that the work performed can be applied to the robustness and imperceptibility conditions.